Towards a Democratic Laboratory School - Perfetti, Simona (European Journal of Social Science Education and Research, 2024)
Nowadays, a new model of democratic school must contemplate educational dimensions capable of realizing those ethical relationships that can face the now unpredictable learning challenges of contemporary global society. Those involved in education have the task of organizing education by taking into account both the differences of each student to enhance the full development of the single individual’s potential, as well as the opportunity to enhance talent to ensure a merit system based not on competitiveness but on recognition of the different skills of each pupil in the class. Perrenoud affirms the importance for the teacher to question himself about his activities and the educational relationship with young people, also with a view to an observation process that the school itself can undertake in the context of an overall self-assessment process.Against this background, the reflection proposed here focuses, in particular, on flipped methodologies, those cognitive and formative processes that, developed within the school of competencies, can be declined in real answers related to the existential, professional and social needs of young people. The transition to this type of school has meant the enhancement of a teaching approach in which pupils take the lead of their own learning pathway, learning to manage those key competences, including digital skills, social and civic competences, which are necessary for personal growth. In the context of these educational issues, it becomes useful to reflect on technology in a broader perspective, not only as a means to learn something but as an "object" able to promote the exploitation of those dimensions of existence, such as cooperation, sense of judgement, and the principle of responsibility, necessary to overcome society’s challenges. Taking a chance on a democratic school means possessing digital wisdom, borrowing an expression from Mark Prensky, namely, that quality that can come out thanks to the enhancement of human capabilities through a balanced use of technologies. The digital wisdom, today’s teacher, will reflexively identify the circumstances in which technology can be a valuable aid to stimulate students’ understanding and creativity. Therefore, a proposal for those involved in education, may be to consider technology in a different perspective which, as Calvani suggests, embraces a different level of technology, the "contour ", the potential, that which can be moved in terms of communication and cooperation. In this sense, flipped technologies (or an inverted way of teaching/learning: a task is given to the class that can be a video to watch, a book to read, or an experience to becarried out , usually to be done at home) such as the Flipped Classroom and the method of the EAS ( method, transforming the school into a laboratory school, can represent an important learning opportunity for the adults of tomorrow. In fact, these technologies, due to their implementation methods, put into effect those values, such as collaboration, reflexivity, sharing, in a learning pathway suitable for living in today’s complex society.